CHICKEN MEAT BALLS WITH BEETROOT (BETA VULGARIS) POMACE POWDER AS FUNCTIONAL INGREDIENT - D. Santhi; A. Elango; A. Kalaikannan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Emulsion based chicken meat balls were prepared with the addition of beetroot pomace powder (BPP) at levels of 1%, 2% and 3%, over and above the amount of meat along with a control without BPP, and the physico-chemical and sensory properties were assessed. Addition of BPP significantly increased the emulsion pH and non significantly increased product pH and emulsion stability. Product yield of 3% BPP incorporated chicken meat balls were significantly higher as compared to other treatments and control. Sensory evaluation scores were significantly higher in 1% BPP incorporated chicken meat balls followed by 2% and 3% BPP incorporated chicken meat balls. From this result, it is concluded that emulsion based functional chicken meat balls could be fortified with dietary fibre content by the inclusion of beetroot pomace powder up to a level of 3% without affecting the physico-chemical and sensory qualities.